The Effect Of Fe Tablet And Date Palm On Improving Hemoglobin Level Among Pregnant Women In The Third Semester - Febry Mutiariami Dahlan; Qomariah Ardhi (Faculty of Medicine, Universitas Andalas, 2021)
Anemia is a nutritional problem with a high prevalence in the world. Basic Health Reseacrch in 2018, around 48,9% of pregnant women in Indonesia experience anemia. This shows that anemia in pregnant women  is still a public health problem because the proportion  is quite high compared to the results of the 2013 Basic Health Research, which amounted to 37,1%. This research aims to identify the effect of Fe tablet and date palm on improving hemoglobin level among pregnant women in the third semester  at the Rita Marningsih Clinic 2020. This study was quasy-experiment by using two group pre-test and post-test and used dependent t test with control group. There were 30 respondents and purposive sampling was conducted, and an independent t-test was used to data analyzed.The Result  revealed that the experimental group the number of pregnant women whose Hb levels increased by 14 people (93,33%) and which decreased by 1 respondent (6,67%) and in the control group 13 respondents experienced an increase (86,67%) and 2 respondents (13,33%) decreased Hb levels. The bivariate result showed that the p value was 0,044<0,05, which means that there was an effect of giving Fe tablets and dates to the hemoglobin levels of pregnant women. Conclusion and recommendation : Fe tablets and dates affect the increase in hemoglobin levels. For pregnant women it is recommended to consume Fe tablets regularly and maintain the nutrition of their food, one of which adds dates to food consumed.